Tupistra khangii (Asparagaceae), a new species from northern Vietnam - Vislobokov, Nikolay A.; Тanaka Noriyuki; Averyanov, Leonid V.; Nguyen, Hiep Tien; Nuraliev, Maxim S.; Kuznetsov, Andrey N. (Phytotaxa, 2014)
Tupistra khangii (Asparagaceae) is described and illustrated as a new species from mountain areas in northern Vietnam. It is distributed widely in north-western Vietnam and adjacent territories.